A quantitative approach to the socio-economic valuation of pollinator-friendly practices: a protocol for its use - Garibaldi, Lucas Alejandro (2016)
In agro-ecosystems, pollinators are essential for orchard, oilseed crops, horticultural and forage production, as well as the production of seed for many root and fibre crops. Pollinators such as bees, birds and bats affect 35 percent of the world?s crop production, increasing the outputs of 87 of the leading food crops worldwide, plus many plant-derived medicines for the world?s pharmacies. Pollinators contribute significantly to human health; pollinator dependent crops supply major proportions of micronutrients. In terms of ecosystem health, approximately 90 percent of wild plants rely on pollinators that support wider biodiversity.